Early Patellofemoral Osteoarthritis Features One Year After Anterior Cruciate Ligament Reconstruction: Symptoms and Quality of Life at Three Years. Issue 6 (26th May 2016) - Culvenor, Adam G.; Collins, Natalie J.; Guermazi, Ali; Cook, Jill L.; Vicenzino, Bill; Whitehead, Timothy S.; Morris, Hayden G.; Crossley, Kay M.
Abstract : Objective: To determine whether the presence of magnetic resonance imaging (MRI) osteoarthritis (OA) features in the patellofemoral or tibiofemoral joint (i.e., bone marrow lesions, cartilage lesions, and osteophytes) and/or functional impairments, 1 year following anterior cruciate ligament reconstruction (ACLR), can predict Knee Injury and Osteoarthritis Outcome Score (KOOS) at 3 years. Methods: A total of 93 participants (56 [60%] men, mean ± SD age 29 ± 9 years) who had undergone MRI examination and functional testing at 1‐year post‐ACLR, completed the KOOS at 3 years postsurgery. Multivariate regression models evaluated the prognostic capacity of compartment‐specific osteochondral OA features, scored using the MRI Osteoarthritis Knee Score, and functional performance (hop for distance, 1‐leg rise), to predict outcome on 4 KOOS subscales (pain, symptoms, sport/recreation, and quality of life [QOL]). Results: Presence of patellofemoral cartilage lesions 1‐year post‐ACLR predicted worse score on all KOOS subscales at 3 years ( P ≤ 0.01). Regression coefficients (B) were −5.1 (95% confidence interval [95% CI] −9.1, −1.2) for symptoms, −4.0 (95% CI −6.7, −1.4) for pain, −6.7 (95% CI −11.0, −2.4) for sport/recreation, and −8.6 (95% CI −15.1, −2.1) for QOL. No significant associations were found between tibiofemoral MRI features and knee symptoms. Poorer performance on the 1‐leg‐rise test predicted worse KOOS‐QOL (B −6.5 [95% CI −12.4, −0.5], P = 0.03). Conclusion: The presence of a patellofemoral articular cartilage lesion and lower 1‐leg‐rise performance at 1 year postsurgery are prognostic for poorer 3‐year outcome following ACLR. Particular attention to patellofemoral compartment lesions and functional capacity is warranted during postoperative rehabilitation programs, as these features represent potential targets for therapy aimed at minimizing symptomatic disease progression in these young adults.